FRI0339 LONG-TERM EFFICACY OF THE ORAL SELECTIVE JANUS KINASE 1 INHIBITOR FILGOTINIB IN PSORIATIC ARTHRITIS: WEEK 52 RESPONSE PATTERNS IN INDIVIDUAL PATIENTS FROM AN OPEN-LABEL EXTENSION (OLE) STUDY (EQUATOR2). (2nd June 2020) - Gladman, D. D.; Coates, L. C.; Van den Bosch, F.; Helliwell, P.; Tasset, C.; Meuleners, L.; Gilles, L.; Gheyle, L.; Trivedi, M.; Alani, M.; Besuyen, R.; Mease, P. J.
Abstract : Background: EQUATOR (NCT03101670 ) was a 16-week, Phase 2, multicenter, double-blind, placebo-controlled, randomized controlled trial (RCT) of filgotinib in patients with active psoriatic arthritis. 1 Filgotinib demonstrated rapid efficacy compared with placebo across multiple domains, including the primary endpoint of Week 16 American College of Rheumatology (ACR) 20 response. 1 Patients completing the RCT could join an ongoing 148-week OLE (EQUATOR2; NCT03320876 ). Objectives: In this prespecified interim analysis at Week 52 of the OLE, individual patient responses with respect to disease activity were evaluated. Methods: Placebo-treated RCT patients switched to filgotinib (200 mg once daily) at Week 16 and entered the OLE; patients previously assigned to filgotinib continued. Individual response patterns at Week 52 of the OLE were evaluated for ACR20/50/70, Psoriatic Arthritis Disease Activity Score (PASDAS) low disease activity (LDA), minimal disease activity (MDA), and MDA/very low disease activity (VLDA). Results: 124 patients (95%) completed EQUATOR; 122 (93%) enrolled in the OLE. At Week 52, 11 patients (9%) had discontinued treatment in the OLE. Median (range) exposure to filgotinib was 66.0 (0.4–104.1) weeks. In patients originally assigned to filgotinib, sustained efficacy was seen through to OLE Week 52 for ACR20, 50, and 70; PASDAS LDA; MDA (Table; Figure 1 a ); and MDA/VLDA. In total, 77% and 93% of those achieving MDA and ACR50 response in the RCT period maintained this at Week 52 (Table ). A substantial proportion of RCT non-responders also achieved a treatment response in the OLE, meeting MDA and ACR50 criteria (22% and 37%, respectively; Table ). Response patterns in the OLE were similar regardless of prior RCT treatment. In total, at Week 52 of the OLE, 33.6% of patients achieved MDA response (Figure 1 a ); 55.0% achieved ACR50 response. Figure 1 b shows individual patient response over time for MDA. Conclusion: Data from this 52-week OLE interim analysis suggest that further improvement in disease activity can be expected with filgotinib beyond 16 weeks in patients with active psoriatic arthritis. Sustained efficacy was demonstrated across several measures of disease activity, including MDA and ACR50. References: [1]Mease P, et al. Lancet 2018;392:2367–77. Acknowledgments: EQUATOR and EQUATOR2 were sponsored by Galapagos NV and co-funded by Galapagos NV and Gilead Sciences. Medical writing support was provided by Hannah Mace MPharmacol, CMPP (Aspire Scientific Ltd, Bollington, UK) and funded by Galapagos NV. Disclosure of Interests: Dafna D Gladman Grant/research support from: AbbVie, Amgen Inc., BMS, Celgene Corporation, Janssen, Novartis, Pfizer, UCB – grant/research support, Consultant of: AbbVie, Amgen Inc., BMS, Celgene Corporation, Janssen, Novartis, Pfizer, UCB – consultant, Laura C Coates: None declared, Filip van den Bosch Consultant of: AbbVie, Celgene Corporation, Eli Lilly, Galapagos, Janssen, Novartis, Pfizer, and UCB, Speakers bureau: AbbVie, Celgene Corporation, Eli Lilly, Galapagos, Janssen, Novartis, Pfizer, and UCB, Philip Helliwell: None declared, Chantal Tasset Shareholder of: Galapagos (share/warrant holder), Employee of: Galapagos, Luc Meuleners Employee of: Galapagos, Leen Gilles Consultant of: Galapagos, Lien Gheyle Employee of: Galapagos, Mona Trivedi Shareholder of: Amgen and Gilead Sciences, Employee of: Gilead Sciences, Muhsen Alani Employee of: Gilead Sciences, Robin Besuyen Shareholder of: Galapagos, Employee of: Galapagos, Philip J Mease Grant/research support from: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Eli Lilly, Novartis, Pfizer, Sun Pharmaceutical, UCB – grant/research support, Consultant of: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Eli Lilly, Novartis, Pfizer, Sun Pharmaceutical, UCB – consultant, Speakers bureau: Abbott, Amgen, Biogen Idec, BMS, Eli Lilly, Genentech, Janssen, Pfizer, UCB – speakers bureau